Optimization of Epidemic Survey and Epizootics Prognostication in Kyzylkum Autonomous Plague Focus in Modern Conditions within Uzbekistan - G. R. Bazarova; A. S. Nematov; O. A. Husanov; S. . Ahmadbek Kizi (Проблемы особо опасных инфекций, 2009)
Kyzylkum autonomous plague focus, the large part of which is situated on the territory of the Republic of Uzbekistan, has always been distinguished as regards periodic development of acute extended epizootics and occurrence of epidemic complications. Epidemic survey includes the wide reconnaissance with visual evaluation of epizootiological factors and material collection out of fresh pellets for serological analysis. In case of discovery of carriers carcasses, suspected as plague infected, the collection of samples into spiritus in view of their further PCR analysis is carried out.